Does problem based learning through outdoor learning enhance creative thinking skills? - Lia Auliandari; Erie Agusta; Siti Esa Bintari (JURNAL BIOEDUKATIKA, 2019)
Studies of PBL and outdoor learning in improving creative thinking skills in Indonesia are still conducted separately. Although there are studies that combine PBL with outdoor learning, the dependent variables are still learning outcomes and motivation, not yet reaching creative thinking ability. This study aimed to determine the influence of the PBL model through outdoor learning in improving students' creative thinking ability on Environmental Changes at grade X SMA PGRI Tanah Abang PALI. This study used the quasi-experimental design (using nonequivalent control group design) the sampling technique used purposive sampling. The instrument used essay questions consisting of aspects of fluency, flexibility, originality, elaboration, and evaluation. The descriptive data analysis used gain score and inferential data analysis used independent sample t-test supported by the effect size r independent t-test. The results showed there was the influence of the PBL model through outdoor learning to improve students' creative thinking ability on Environmental Changes at grade X SMA PGRI Tanah Abang PALI (sig 0,00 < ± 0,05/2). The limitation of this study is the determination of the observation location of pollution objects. If the PBL model through outdoor learning wants to be used, the purpose of the observed problem should be a more real problem and directly to the location of pollution, so that outdoor learning becomes more optimal.